Microplastic and mesoplastic in stagnation of the Vistula water in highly urbanized areas of the Krakow poviat - preliminary research - Ewa Dacewicz; Tomasz Bergel; Ewa Łobos-Moysa; Katarzyna Moraczewska-Majkut; Witold Nocoń (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to analyze the occurrence of plastic particles in the waters of the Vistula River within Kraków.